2012
DOI: 10.1371/journal.pone.0029259
|View full text |Cite
|
Sign up to set email alerts
|

Plants Can Benefit from Herbivory: Stimulatory Effects of Sheep Saliva on Growth of Leymus chinensis

Abstract: BackgroundPlants and herbivores can evolve beneficial interactions. Growth factors found in animal saliva are probably key factors underlying plant compensatory responses to herbivory. However, there is still a lack of knowledge about how animal saliva interacts with herbivory intensities and how saliva can mobilize photosynthate reserves in damaged plants.Methodology/Principal FindingsThe study examined compensatory responses to herbivory and sheep saliva addition for the grass species Leymus chinensis in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 58 publications
0
53
0
1
Order By: Relevance
“…On the other hand, animal salivary secretions may additionally influence growth and development of certain food plants [69] -a both surprising and exciting hypothesis that has regained scientific interest and produced first supporting data in goats, cattle and sheep in recent years [70][71][72][73]. Salivary growth factors, such as EGF, NGF or TGF, are discussed as the most probable enhancers of plant re-growth [73] and because of their peptide nature they are accessible by proteomic studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, animal salivary secretions may additionally influence growth and development of certain food plants [69] -a both surprising and exciting hypothesis that has regained scientific interest and produced first supporting data in goats, cattle and sheep in recent years [70][71][72][73]. Salivary growth factors, such as EGF, NGF or TGF, are discussed as the most probable enhancers of plant re-growth [73] and because of their peptide nature they are accessible by proteomic studies.…”
mentioning
confidence: 99%
“…Salivary growth factors, such as EGF, NGF or TGF, are discussed as the most probable enhancers of plant re-growth [73] and because of their peptide nature they are accessible by proteomic studies. In a recent study it was found that animal saliva stimulated growth of perennial grasses, accelerating mobilisation of carbohydrates, enhancing buds tillers and consequently increasing biomass [73]. In another study that employed a proteomics approach on rice seedlings, ovine saliva deposition caused the rice to develop a basal defense, i.e.…”
mentioning
confidence: 99%
“…However, both Poa liguralis and Kobresia myosuroides compensated for the shorter leaves, by producing more leaves per tiller. Accordingly, increasing clipping intensity in Leymus chinensis resulted in decreasing final shoot length, and tillering decreased only in 100 %-clipped individuals in one of two studied years, and resulted in a generally lower biomass accumulation in clipped plants (Liu et al 2012).…”
Section: Discussionmentioning
confidence: 86%
“…Socher et al (2013) also found that mowing at intermediate levels generally enhanced plant species richness. Additional under proper stocking densities, grazing promoted plant species richness and plant productivity (Liu et al, 2012;Socher et al, 2013). In order to make full use of limited grassland resources, total porosity increased, and soil particle size distribution also changed after nine years of restoration.…”
Section: Discussionmentioning
confidence: 99%